Response and Readiness of CLC (Community Learning Center) Management in Utilizing ICT During Covid-19 Pandemic. (Journal of Nonformal Education, 2023)
Non-formal education in CLC affected by the Covid-19 Pandemic. The presence of the pandemic has shifted the habit of face-to-face learning processes to face-to-face online using information technology and computers (ICT). This accelerates the transformation of CLC to be more adaptive to the development of the information age, internet of things and sustainable 21st century learning. This study aims to determine the characteristics of CLC in adapting new habits from the management aspect to information technology-based learning. This research approach was carried out qualitatively by conducting in-depth interviews with CLC samples in each district in the city of Yogyakarta. CLC as a non-formal education unit with initiation from, by and for the community has unique characteristics that are flexible. In addition, CLC still has competitiveness over the various negative impacts of the pandemic with various limited resources. These characteristics bring CLC to be an educational alternative that is sought after by students at school age today to provide educational services that suit their needs. Nevertheless, the government's support to provide urgent ICT literacy assistance so that CLC is more qualified and continuously participates in the intellectual life of the nation.